THE USE OF A LARYNGEAL MASK FOR ANESTHESIA IN A PATIENT WITH SEVERE CERVICAL-THORACICCICATRICIAL CONTRACTURE - Sadikova Minura Adkhamovna. (Scholar Express Journals, 2022)
According to the results of our research, we came to the conclusion that the indication for the use of LM involves to conduct the planned surgical interventions in prepared patients. A successful anesthetic procedure, in an inaccessible airway of respiratory tracts and in distortion by post-burn cirrhosis and fibrosis, requires a planned approach to the safety of respiratory tracts. This approach includes a successful use of the laryngeal mask (LM) in conditions of total myoplegia while providing anesthesia in the neck. Timely and effective airway management of the respiratory tracts is a priority for these patients. Our main task is to restore the form and function of this area in a safe way.
Keywords: Airway assessment; airway management; laryngeal mask; intubation technique